Assessment of selected microalgae (Spirulina sp., Nannochloropsis sp. and Chlorella sp.) as feed supplement for Macrobrachium rosenbergii (de Man) juveniles - Mohamad Sukri, Suniza Anis (2017)
A series of experiment were conducted to study the potential of feed formulation for freshwater prawn Macrobrachium rosenbergii juvenile. Study on the potential of selected microalgae (Spirulina sp., Nannochloropsis sp. and Chlorella sp.) as feed for M. rosenbergii juvenile was conducted with amino acid and fatty acid profile. From the results, methionine and tryptophan in amino acid were not detected in Spirulina sp., Nannochloropsis sp. and Chlorella sp. in all four different levels. The arginine, isoleucine, leucine, alanine, aspartic acid and glutamic acid level were high with increasing level of Spirulina sp. Nannochloropsis sp. and Chlorella sp. showed high percentage in leucine, lysine and arginine. For fatty acid analysis, only Spirulina showed a small portion of γ–linolenic acid (GLA). Chlorella showed no detection on Eicosapentaenoic acid (EPA) when compared to Spirulina and Nannochloropsis. For second experiment, a series of experiments were conducted to study the potential of the feed formulations for freshwater prawn Macrobrachium rosenbergii juvenile based on three types of microalgae (Spirulina sp., Nanochloropsis sp. and Chlorella sp.). An experiment in triplicate with prawn (2.5-2.6 g) were fed until an apparent satiation with 32% crude protein diet containing three types of algae with different level (Diet 1= 0 %, Diet 2=2.5 %, Diet 3= 5 % and Diet 4= 10%) in varying algae levels ranging from 0, 2.5, 5 and 10% respectively for 56 days. At the end of the feeding trial, prawn given Diet 4 containing 10 % of Spirulina sp. gave the optimum growth which also contributed to the best feed efficiency. There was no significant difference in FCR in all treatments (p<0.05). There were significant differences (p<0.05) in growth rate among treatments and similarly prawns fed Diet 4 in Spirulina sp. had the highest weight gain (WG) and specific growth rate (SGR) 5.53 g and 2.05 %/day, respectively. The percentage survival of M. rosenbergii ranged from 63-83 %. This study also demonstrated that the nutrient from Spirulina sp. is more suitable to be supplemented in prawn diet compared with Nannochloropsis sp. and Chlorella sp. The used of Cr2O3 marker is reliable for digestibility study. Spirulina sp., Nannochloropsis sp. and Chlorella sp. were analyzed for antimicrobial activity to determine the potential of the algae against the selected pathogens. Chlorella sp. had successfully inhibited Aeromonas hydrophilla followed by A. salmonicida and Vibrio alginolyticus. The maximum inhibition zone by Chlorella sp. were 14.67 mm against A. hydrophila, followed by 11.33 mm against V. alginolyticus and 10.00 mm against A. sobria. Studies on the effect of Spirulina sp, Nannochloropsis sp. and Chlorella sp. on prawn challenged with A. hydrophilla for 48 hours showed there are no significant difference among the different treatments. Prawn’s mortality was 100 % in control group. Spirulina sp. with 10% algae level showed a good potential to be as a feed supplement for M. rosenbergii juveniles. Spirulina sp. contained a variety of amino acids and fatty acids to support good growth performance, digestibility and disease resistance as compared to Nannochloropsis sp. and Chlorella sp.